Increasing measurement accuracy: Scaling effect on academic resilience instrument using Method of Successive Interval (MSI) and Method of Summated Rating Scale (MSRS) - Febriana, Beta Wulan; Setiawati, Farida Agus (Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
A research instrument is crucial and must meet the requirements to be valid and reliable in content and construction. Not infrequently, various methods are tried to increase the accuracy of research instruments, one of them being a simple method such as the scaling technique. This research aims to improve measurement accuracy by using scaling techniques through the process of successive intervals and summated rating scale in confirmatory factor analysis of the Academic Resilience (ARS) instrument. This research is a descriptive exploratory study using a questionnaire consisting of five answer choices (5-point Likert scale) as the research instrument. Participants in this research were 300 students. Data analysis was conducted using Microsoft Excel and R programs. The research results showed that there was a significant difference in the results of the reliability and validity of the constructs as well as the parameters in the confirmatory factor analysis of the ARS instrument before and after transformation with the method of successive intervals and summated rating scale. This research contributes to implementing quantitative data scaling practices in measurement research, and it has been proven that there was an increase in measurement accuracy after scaling.